2018
DOI: 10.1007/s40430-018-1462-4
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven model identification of guided wave propagation in composite structures

Abstract: This paper shows the applicability of data-driven model identification to describe guided wave propagation in composite structures. The model identified can be useful to predict waveform or further conditions considering the dynamics of wave propagation in composites media, mainly when the geometry or boundary conditions are complex and make it very difficult to propose an analytical model. Thus, the main purpose of this paper is to use a simple autoregressive with exogenous terms model to fit the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Figueiredo et al (2012) proved the capability of autoregressive models with eXogenous inputs (ARX) as a sensitive feature for damage detection in a composite plate. Silva (2018) illustrated some practical aspects of the implementation of ARX models using Lamb wave for system identification of a composite plate assuming temperature effects. Moreover, the authors discuss the potential of ARX models regarding the purpose of SHM.…”
Section: Introductionmentioning
confidence: 99%
“…Figueiredo et al (2012) proved the capability of autoregressive models with eXogenous inputs (ARX) as a sensitive feature for damage detection in a composite plate. Silva (2018) illustrated some practical aspects of the implementation of ARX models using Lamb wave for system identification of a composite plate assuming temperature effects. Moreover, the authors discuss the potential of ARX models regarding the purpose of SHM.…”
Section: Introductionmentioning
confidence: 99%
“…Among these approaches, one very effective way to address this issue is by using data-driven model identification based on guided Lamb wave propagation or random inputs provided by PZT active-sensing. In particular, Auto-Regressive (AR) models to describe Lamb waves are already abundantly used in the SHM of composite structures (da Silva, 2018; Figueiredo et al, 2012; Nardi et al, 2016; Paixão et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Figueiredo et al (2012) showed the use of time-series predictive models for piezoelectric active-sensing using autoregressive with exogenous input (ARX) models and machine learning to detect damages. da Silva (2018) also applied the ARX model to perform predictions, and a waveform generator in a 10 layers carbon-epoxy plate excited by guided Lamb waves assuming different central frequencies and environmental conditions, such as temperatures changes, and noted some benefits and disadvantages of the possible performance of this strategy for SHM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, composite materials have been used in different industrial applications due to their features such as lightweight, high strength-to-weight ratio, and long-term durability. However, the level of requirements in SHM of these materials is more complicated compared with metallic structures due to complex damage, such as matrix cracks, delamination, and debonding, and significant effects of load variations in service life [14].…”
Section: Introductionmentioning
confidence: 99%